Health care workers' perception of the internet and mobile technologies in Colombia (2009)
In July 2007 in Medellín, Colombia, 1 200 health care professionals were asked to complete a questionnaire: of the 493 who participated, the mean age was 31.2 years; 58.8% were physicians; and 97.6% had Internet access, 60.5% on a daily basis and 27.7%, weekly. The preferred place to access the Internet was from home (58%) or from the work place (12.5%); 98% reported having a cell phone, and of those, 80% were interested in using health education tools via cell phone. These are the first data published regarding Internet and cellular phone penetration among health care workers in Colombia. Acceptance of the Internet and mobile systems as health information tools is gaining, and as such, creating a new opportunity for training and harnessing of these new technologies.